Designing New Funding Models for Russian Football Clubs - Ilia Solntsev (Корпоративные финансы, 2019)
In Europe, most football clubs have long been positioned as business projects, which are active in financial markets and apply various funding tools. The 2018 FIFA World Cup inspired a new wave of interest in Russian football and created attractive conditions for applying new funding tools. The specifics of the economy surrounding sports development in Russia have led to a situation whereby most sports clubs depend on limited apportionments of budgetary funds, and require novel sources of additional funding for different development purposes, e.g. constructing stadiums, training grounds, youth academies and everyday operations.